MODERN CONCEPTUAL PRIORITIES OF CULTURAL ANTHROPOLOGY - Nikolay N. Polosin (Вестник Северо-Кавказского федерального университета, 2022)
The article is devoted to the problems of the contemporary status and conceptual priorities of the cultural anthropology. This scientific discipline, having a high speculative potential, covers a wide range of questions, connected with the functioning of the national cultures, the development of interaction between different ethnic communities, national models of the world. The article describes the main progressive principles of cultural anthropology, its role in the system of the Humanities.